Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

simplify the expression

-7 - 8y + 1 - 2y = ?


Sagot :

MattD
In this expression, you must first arrange all the elements, so that you could see where to unknowns, and where not. Then you need to add or subtract like terms. After this we get the result as below.

-7 - 8y + 1 - 2y = ?

-8y - 2y - 7 + 1 = -10y -6

-7-8y+1-2y

=-7+1-8y-2y

=-6-10y